2015
DOI: 10.1161/circinterventions.114.001392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Coronary Atherosclerosis and Outcomes of Percutaneous Coronary Intervention

Abstract: O besity contributes to the development and progression of coronary artery disease and adverse events, in part, by reducing insulin sensitivity and promoting basal sympathetic tone, hypercoagulability, and systemic inflammation. 1,2 Conversely, in patients with established coronary artery disease, the effect of obesity on clinical outcomes remains controversial. [3][4][5][6] Recent studies suggest that an increased body mass index (BMI) is associated with a decreased mortality and major adverse cardiac events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
(34 reference statements)
0
10
1
Order By: Relevance
“…The performance of coronary interventions in obese patients has steadily increased during the last few decades 31 and has been shown to be associated with fewer repeated revascularizations in obese patients than non-obese patients, possibly due to a larger external elastic membrane that preserves the lumen dimensions, larger stent area, and presence of beneficial vasoactive properties that may offset the adverse effects of excess adipose tissue. 32 In the current study, we were unable to demonstrate the existence of the obesity paradox in our PCI population. Periprocedural complications during the hospital stay, the length of hospitalization, and the incidence of major adverse cardiovascular events at 1 year were not different between the obese group and the other two groups.…”
Section: Discussioncontrasting
confidence: 57%
“…The performance of coronary interventions in obese patients has steadily increased during the last few decades 31 and has been shown to be associated with fewer repeated revascularizations in obese patients than non-obese patients, possibly due to a larger external elastic membrane that preserves the lumen dimensions, larger stent area, and presence of beneficial vasoactive properties that may offset the adverse effects of excess adipose tissue. 32 In the current study, we were unable to demonstrate the existence of the obesity paradox in our PCI population. Periprocedural complications during the hospital stay, the length of hospitalization, and the incidence of major adverse cardiovascular events at 1 year were not different between the obese group and the other two groups.…”
Section: Discussioncontrasting
confidence: 57%
“…In detail, a recent intravascular ultrasound study performed in patients with stable CAD or ACS found a greater plaque burden and plaque area, as well as higher incidence of plaque rupture, in patients with higher BMI compared with patients with lower BMI. 25 A non-invasive study investigating the relationship between coronary plaque characteristics by computed tomography (CT)-coronary angiography and visceral adipose tissue, observed a significant association between the latter and the amount of prothrombotic status induced by DM-associated metabolic abnormalities. 9 Interestingly, a recent study enrolling both diabetic and non-diabetic patients with their first ACS showed that high glycemic variability was associated with increased plaque vulnerability in non-culprit lesions.…”
Section: Obesity Overall Plaque Burden and Plaque Phenotypementioning
confidence: 99%
“…The BMI of our population was lower than those of Raber and colleagues (27.5±3.8 kg/m 2 ) and Zhao and colleagues (27.0±2.4 kg/m 2 ). A relationship between high BMI and plaque progression has been reported 29,30. Second, 90% of patients in the STEMI group were new statin users.…”
Section: Discussionmentioning
confidence: 90%